al Mu'jam al mufahras li al faz al hadith al nabawiy : an al kutub al sunnah wa an musnad al Darimi, Muwatta' Malik, wa Musnad Ahmad Ibn Hanbal - I.J. Wensinck (Dar al Da'wah, 1987)
ws.jl.1.c.1-3, jl.2,6-7.c.1-2,jl.3-5,8.c.1/stoc1, jil.2,c.3 ; jil.3,c1-3 ; jil.4,c.2-4 ; jil.5,c.2-5 ; jil.6,c.1-2,4 ; jil.7,c.1-4 ; ji;8,c.2/stoc4, jil.1=c.1-2/stoc5,jil.2,c3,jil.4.c4